Ao haru ride. 8 - Sakisaka, Io (Shojo beat manga., 2020)
Futaba Yoshioka has encountered her first love again in high school, but he seems different from the boy she once knew. Wanting closure, Futaba decides to confess to Kou and hear his response. Meanwhile, Toma has decided it<U+2019>s time for him to pursue Futaba.